Upaya Membangkitkan Motivasi Belajar Pendidikan Agama Islam Tingkat Anak-anak pada Masa Covid-19 di Gampong Jeulingke dengan Penerapan Komunikasi Persuasif - Prilli Prisiska; Syahril Furqany (Jurnal Riset dan Pengabdian Masyarakat, 2021)
Early childhood was realized as an asset for the future of the nation, parents and society. The tremendous responsibility that parents must carry out is at the stage of development. In addition, children's happiness is a significant factor in the development of children, both at home and outside the home. Therefore, parents must create a safe, comfortable, harmonious and loving environment in the family to strengthen the emotions between parents and children, especially during the COVID-19 pandemic, which requires children and parents to stay at home. This research is qualitative research with research methods carried out using literature (library), both in the form of books, notes, and reports of previous research results, and this study uses library research methods. The study results indicate that during the COVID-19 pandemic in online learning, students can become less active in conveying their aspirations and thoughts, which can result in boring learning. A student who experiences boredom in learning will get progress in learning outcomes. Therefore, it is necessary to encourage students to move students so that they are enthusiastic about learning to have learning achievements.